Efficacy and Safety of Miltefosine in Treatment of Post-Kala-Azar Dermal Leishmaniasis - Shyam Sundar; Anup Singh; Jaya Chakravarty; Madhukar Rai (The Scientific World Journal)
Background. Long regimens for the treatment of post-kala-azar dermal leishmaniasis (PKDL) result in noncompliance. A safe, effective, and acceptable regimen for the treatment of PKDL is still to be developed. Miltefosine has been found to be effective in the treatment of Visceral Leishmaniasis (VL). Hence, its efficacy was tested in patients of PKDL. Methods. In this exploratory study, 33 patients with PKDL aged 10 years and above were administered miltefosine (50 mg for those weighing <25 kg or 100 mg in divided doses for those ≥25 kg and 2.5 mg per kg for children) for 12 weeks and followed up for one year to find out the efficacy. Results. Out of 33 patients, 3 patients withdrew consent. Treatment was stopped due to adverse effect in 1 patient. 28 (96.6%) got cured with complete disappearance of lesion while 1 patient (3.4%) failed treatment by protocol analysis. Conclusion. Miltefosine was found to be effective and safe in the treatment of PKDL.